دور النشاط البدني في التخفيف من القلق الاجتماعي لدى ذوي الإعاقات الحسية (Comprehensive Journal of Science, 2025)
Anxiety Levels in Individuals with Sensory Impairments (Blind and Deaf).This theoretical study addresses the dual challenge faced by individuals with sensory impairments (blind and deaf) concerning their elevated rates of Social Anxiety, often stemming from communication barriers and environmental obstacles. The study aims to establish and analyze the mechanisms through which regular and adapted physical activity is theoretically expected to contribute to reducing these anxiety levels. The theoretical framework is grounded in a two-level analysis of the mechanisms: The Physiological Mechanism, where physical activity promotes the release of calming neurotransmitters (like serotonin and endorphins) and regulates the stress axis (HPA Axis) to reduce the physiological arousal of anxiety; and the Psychological Mechanism, where activity enhances Self-Efficacy and Positive Body Image, thereby breaking the cycle of Self-Focused Attention, which is central to social anxiety. The study presents a Progressive Reference Framework for adapted physical programs that accounts for the specificity of each impairment (such as relying on acoustic signals for the blind and visual cues for the deaf) to ensure effective inclusion. The study recommends adopting this theoretical framework as a guide for developing specialized sports intervention programs to enhance the psychological resilience and social competence of this populati.